An interview with board member Serdar Sariciftci. (10th March 2015) - Grüner, George; Tyrrell, James
Abstract : Fundamental science must be nurtured for technological success to prevail, emphasizes Serdar Sariciftci, head of the Linz Institute for Organic Solar Cells at Johannes Kepler University in Austria. In this interview with Translational Materials Research, he shares his experience as an academic and entrepreneur in the field of renewable energy to examine what it takes to translate materials breakthroughs into market-ready devices.